Quantifying and Comparing the Hyperelastic Properties of Skin, Leather and Silicone - Adam Mohd Adnan, Zurri; Azman Yahaya, Mohd; Nor Fazli Adull Manan, Mohd; Mahmud, Jamaluddin (International Journal of Engineering and Technology, 2018)
Skin is the largest and an important organ of an animal or human body. Skin provides multiple important functions and it exhibits complex behaviour. The injuries due to burn, damage and accident have led to research in understanding skin behaviour as this knowledge could lead to producing good quality of synthetic skin. To date, the properties of skin are still not well quantified. Therefore, this study aims to quantify and compare the hyperelastic properties of skin, leather and silicone using three common hyperelastic constitutive models which are Neo-Hookean, Mooney-Rivlin and Ogden model. The specimens were prepared using specimens template according to ASTM D2209 testing standard and tested under uniaxial tension with speed rate of 254 mm/min. The numerical analysis was performed to quantify and determine the hyperelastic material constants using the selected hyperelastic constitutive models. The material constants were determined using Excel (solver) and curve fitting technique was used to match the stress-stretch curve to experimental data. The results show that the Mooney-Rivlin model produces the best fit curve for all three specimens. Hence, it can be concluded that all the three hyperelastic models, especially Mooney-Rivlin are capable to determine the mechanical behaviour of skin, leather and silicone rubber.Â